A proposed model for nonlinear analysis of RC beam-column joints under seismic loading. (1st February 2019) - Zhao, Wentong; Yang, Hong; Chen, Jinfeng; Sun, Panxu
Highlights: Proposed a component based beam-column joint model. Strut and tie within joint were represented by the springs in the proposed model. The effects of axial force, strut and truss mechanism were calculated in each iteration step of numerical simulation. Reasonable strength reduction model and bar slip model were used for simulation. Simulated hysteretic responses agree well with test results. Abstract: Beam-column joints are generally subjected to significant inelastic deformations and considerably contribute to storey drifts under seismic loading. It is vital to consider joint shear deformation and longitudinal bar slip in the finite element simulation, and neglecting these effects will lead to misleading results. A new macro beam-column joint element model was proposed to consider the influence of joint inelastic deformations for interior joint with stirrups. The proposed macro beam-column joint was developed based on the force transfer mechanisms and inelastic response mechanisms, using axial springs representing bar-slip mechanism of longitudinal reinforcement, concrete and reinforcement in the joint core and interface-shear. In the joint core, eight concrete components and eight reinforcement components worked together to contribute to the effect of joint shear deformation. Constitutive relationship was developed to define the response of proposed joint model based on the dimensions, geometric, and material properties. An applicable model was used for simulating strength reduction of confined concrete strut due to joint damage and cyclic load history. Modifications were made to provide a more reasonable simulation of the anchorage zone response. The numerical analysis results were compared with experimental data of six beam-column subassemblages to validate the proposed macro beam-column joint element model. The comparison between the simulated and the test results shows that the proposed joint model is able to simulate the hysteretic response, joint shear strength and joint shear deformation of the beam-column subassemblages. Additionally, the comparison of the simulated results between proposed joint model and available joint model indicates that the proposed joint model is more accurate and efficient.